Hexane-1,6-diammonium bis(pyridine-2-carboxylate) - Kim, Nam-Ho (International Union of Crystallography, 2009)
The title compound, C(6)H(18)N(2) (2+)·2C(6)H(4)NO(2) (−), consists of a doubly protonated hexamethylenediammonium dication and two pyridine-2-carboxylate anions. These ions interact by means of intermolecular N—H⋯O and N—H⋯N hydrogen bonds to form a two-dimensional array. The carboxylate groups of the anions appear to be delocalized on the basis of the C—O bond lengths.